BIOSPHERE AND NOOSPHERE: INTERRELATIONSHIPS AND PROBLEMS - Panjiev Suhrob (American Journals, 2024)
In the article, opinions are expressed about the biosphere and noosphere, their interrelationship, the problems that have arisen within the framework of the interrelationship of the biosphere and noosphere, and how to eliminate these problems.